Mohammed Ali, ʿƎmanini (“Trust me”): Linguistic features of a novel in Tigre - Lusini, Gianfrancesco (Aethiopica, 2007)
The novel ʿƎmanini (“Trust me”) by Mohammed Ali Ibrahim Mohammed (born 1966) is the first work written in Tigre by a native speaker. This is a true literary and linguistic experiment, which will greatly enrich our knowledge of the Tǝgrāyǝt grammar and vocabulary, specifically its little known variant spoken among the Beni ʿAmǝr. Several phonetic, morphological, syntactical and lexical peculiarities of the text are here examined in order to reveal whether they are dictated by linguistic constraints (lexico-semantic, grammatical or pragmatic), or have been chosen by the author as stylistic devices for reasons of expressiveness. Passages of ʿƎmanini are here published, translated and commented.